2021
DOI: 10.3928/24748307-20201117-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy: An Interactive Outcome Among Secondary Students in Beijing

Abstract: Background: Health literacy enables a person to make good decisions regarding health care, disease prevention, and health promotion to maintain and improve health. Although health literacy research in China has gained increasing attention in recent years, most existing studies focus on adults rather than adolescents. In addition, little theory-driven empirical research has been conducted to fully understand the relationship among health literacy, its influencing factors, and health outcomes scored on a skills-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
0
10
1
1
Order By: Relevance
“…Meanwhile, Guo et al (2021) found that sociodemographic factors (gender, education, income, and access to information) were not directly related to health literacy. Social-democratic relationships were observed through personal factors such as self-efficacy, social support, and health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Guo et al (2021) found that sociodemographic factors (gender, education, income, and access to information) were not directly related to health literacy. Social-democratic relationships were observed through personal factors such as self-efficacy, social support, and health status.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is the initial component of obtaining a permanent health culture and optimal health status (Barton et al, 2018). Health literacy allows a person to make a good decisions on health care, disease prevention and health promotion to maintain and improve health (Alsubaie & Salem, 2019;Guo et al, 2021). Adequate health literacy will improve healthy lifestyle behaviours and increase individual capacity to manage disease conditions (Coşkun & Bebiş, 2019; M. T. Kim et al, 2020;Mosley & Taylor, 2017).…”
Section: Implications and Role Of Nurses In Healthmentioning
confidence: 99%
“…Penelitian-penelitian tersebut menunjukkan bahwa literasi kesehatan remaja bukan hanya kemampuan seseorang untuk melindungi kesehatannya, tetapi juga merupakan hasil interaksi dengan lingkungan di luar dirinya (Dudley, Bergen, McMaugh, & Mackenzie, 2018;Shuaijun Guo, Yu, Davis, Armstrong, & Naccarella, 2021). Remaja milenial dengan tingkat ekonomi menengah atas sudah terbiasa bermain dengan gadget, yang menyuguhkan berbagai informasi.…”
Section: Pendahuluanunclassified
“…The ecological theory highlights that health literacy is not only an individual’s capability to protect and maintain health but also an interactive outcome with the broader environment [ 30 ]. Except for socio-demographics, empirical studies have shown that other intrapersonal, interpersonal and environmental factors are also associated with child health literacy [ 31 , 32 , 33 ]. Examples of these factors are personal self-efficacy [ 33 ], health interests [ 34 ], social support [ 31 ], and school environment [ 35 ], which also influence children’s physical, cognitive, and educational outcomes.…”
Section: Introductionmentioning
confidence: 99%